2007
DOI: 10.1111/j.1745-7599.2007.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies used by parents of children with autism

Abstract: It is imperative for nurse practitioners (NPs) to provide appropriate professional support and other social support systems to families with children with ASD. Educating parents to sound therapy approaches to provide them with the skills needed to directly address stressful events in order to increase the parent's confidence level as to avoid passive appraisals is also a crucial role of the NP. NPs may want to use the F-COPES as part of the assessment to ascertain the areas of needs of families. This study rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
157
1
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(186 citation statements)
references
References 17 publications
7
157
1
11
Order By: Relevance
“…Specifically, results indicated that parents of youth with ASD were generally more tolerant of disruptive behaviors, whereas parents of non-ASD youth were more intolerant of disruptive behaviors. As discussed previously, parents of youth with ASD are more likely to report a passive appraisal for coping and view behaviors as less modifiable (Bessey et al 2013;Twoy et al 2007). These beliefs may contribute to the parents developing a higher tolerance for misbehaviors.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Specifically, results indicated that parents of youth with ASD were generally more tolerant of disruptive behaviors, whereas parents of non-ASD youth were more intolerant of disruptive behaviors. As discussed previously, parents of youth with ASD are more likely to report a passive appraisal for coping and view behaviors as less modifiable (Bessey et al 2013;Twoy et al 2007). These beliefs may contribute to the parents developing a higher tolerance for misbehaviors.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, parents of youth with ASD often report high levels of disruptive behaviors; however, it is possible that parents do not view these as problematic as they have a rationale for why the behaviors occur. This rationalization may lead these parents to avoid conflicts with the child and accept the difficult issues (Twoy et al 2007). This result may carry undesirable consequences, as increased tolerance could lead to the subsequent reinforcement of negative behaviors, thereby impeding the child's ability to function effectively (Brestan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D'autres travaux sur des groupes ethniques montrent l'influence des facteurs culturels sur les stratégies d'adaptation des parents avec un enfant autiste. Twoy et al (2007) soulignent une plus grande capacité de recadrage chez les parents asio-américains que chez les parents euro-américains, avec un plus grand recours au soutien spirituel chez les parents d'origine asiatique. Comparant la détresse psychologique de parents d'origines hispanique et euro-américaine, Magana et al (2006) montrent que le groupe hispanique présente une détresse psychologique moins importante, associée à une plus grande satisfaction des parents dans la cohabitation avec leur enfant autiste.…”
Section: Résumé De L'articleunclassified